Convergence properties and an inversion formula for the Lambert transform - Miller, E. L. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The object of the present paper is to discuss certain convergence properties of the Lambert transform and to develop an inversion technique. The properties given here are necessary in the application of this transform to integral equations, differential equations and methods of analytic continuation of power series.